Effects of Educational Attainment and Housing Condition on Self-Rated Health in Old Age: Heterogeneity and Tendency in China - Yuan Yao; Shun Zhang; Aihong Li (Frontiers Media S.A., 2022)
In China, the health of the elderly has long been discussed, but few have investigated the diversity of the aging pattern in later life of this population. Although a large body of literature has approved the positive association between socioeconomic status (SES) and health, it still remains controversial regarding whether the association becomes convergent or divergent in old ages. Using data from China's 2010 and 2015 Inter-census Survey (1‰ sample), this paper explored the role of two key SES indicators, educational attainment and housing condition in modifying the self-rated health of Chinese elders aged 60 and above. We observed the diversified patterns of how educational attainment and housing condition have made an impact on the health of these elders in their old age and the temporal changes of the two SES indicators. We found higher educational attainment and better housing condition can lead to higher self-rated health. This positive significance however diminished with age over time, as we observed from 2010 to 2015, indicating the convergent effects of SES on health in old age. We also found that although educational attainment and housing condition were both positively correlated with health, their effects were differentiated. The influence of educational attainment on health waxed, whereas on housing conditions waned over time. These findings suggested the heterogeneity of health and SES effects among Chinese elders.